Study of Cocos Nucifera L. (coconut) shell activated carbon for the removal of methylene blue in aqueous solution - Izzaty Inu (2017)
Activated carbon (AC) was obtained from carbonaceous raw material that normally prepared through carbonization and activation process in certain conditions. The purpose of this study was to investigate the potential application of coconut shell activated carbon as methylene blue (MB) removal from aqueous solution. The carbonization process was a process converting the raw materials to char involving temperature 300 to 500oC. In the activation process, the pore size increased when impregnating with phosphoric acid, H3PO4 as acid activating agent and sodium hydroxide, NaOH as basic activating agent. The pore size of CSAC was characterized by using X-Ray Diffraction (XRD) for phase identification and Fourier transform infrared spectroscopy (FTIR) for detecting functional group that present in CSAC. After that, the kinetic study was investigated in order to determine the percentages removal of dyes (MB) once the adsorbent (CSAC) was introduced to the adsorbate (MB). It can be concluded that increasing the amount of CSAC also showed increment of dye removal. The results indicated that the coconut shell activated carbon could be employed as a low cost alternative in controlling wide range of sorption processes.